The Role of Customary Law in the Management and Protection of Customary Forests in the National Capital City (IKN) - Salsabila, Ameera Najma; Christian, Benedict Philip; Subagijo, Kevin Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Customary forests in the National Capital City (IKN) have an important role in the ecological, cultural and social sustainability of local communities. This research aims to examine the role of customary law in the management and protection of customary forests in the National Capital City (IKN). The method used in this research is the normative juridical method, namely by examining or analyzing secondary data consisting of literature and journals that discuss indigenous peoples and their customary rights. The application of customary law in the National Capital City (IKN) has provided a strong legal foundation for indigenous communities to safeguard their forests from illegal activities and adverse environmental changes. The research also identifies challenges and conflicts that arise in the implementation of customary law, including tensions with national law. The results of this study provide a deeper understanding of how customary law plays a role in the management and protection of customary forests in the National Capital City (IKN).